Encuesta multidisciplinaria en Curré: informe preliminar - Bickmore, Lee (2013)
The goal of the report that we present in the following has for its objective to make known preliminary results obtained by an Anthropology Team, based ona series of surveys taken in the indigenous community of Curré, cantón Buenos Aires, Costa Rica. The investigators focussed on a series of socio-cultural themes as they were recordedin this Indigenous community: social organization, economic resources, languages, recent revitalization, political elections.